Matrix metalloproteinase-9 index as a possible parameter for predicting acute coronary syndrome in diabetics - Popović, Srdjan; Canović, Fadil; Ilić, Miroljub; Rafajlovski, Sašo; Dimitrijević-Srećković, Vesna; Matanović, Dragana; Vujović, Svetlana; Djordjević, Predrag; Gostiljac, Draško (Vojnosanitetski pregled, 2015)
Background/Aim. Matrix metalloproteinase-9 (MMP-9) index is the ratio of active MMP-9 and total MMP-9 levels. It reflects the importance of MMP-9 in acute coronary syndrome (ACS). Methods. The study included 3 groups of patients (n = 87): the group 1 – non-diabetic subjects without ACS (control); the group 2 – diabetic patients with ACS [subgroups with unstable angina pectoris (UAP), myocardial infarction (MI) or reinfarction]; and the group 3 non-diabetics patients with ACS. Total and active MMP-9 were measured and used to create MMP-9 index. Results. MMP-9 index, as a marker showed good sensitivity and specificity, of ACS in diabetics, with a cut-off value over 58.2. MMP-9 was higher in the study groups than in the control one. MMP-9 correlated with ACS occurrence and type of cardiovascular event. A statistically significant difference was found among the groups according to active MMP-9 (p < 0.001). The same was found with active MMP-9 between the control and the group with MI (p < 0.001). The control was highly statistically significantly different from the group of patients with UAP (p < 0.01). Statically significant differences in MMP-9 index was found between the control and the diabetics with ACS (p < 0.001). Statistically significant difference of MMP-9 index was also found in the controls compared to the value in non-diabetic patients with ACS (p < 0.01). Conclusion. MMP-9 index may be a possible marker of atheromatous plaque rupture in diabetics.
Keywords: diabetes mellitus; acute coronary syndrome; matrix metalloproteinase 9; prognosis